(3cJGH GdJThjb HWQjb GdJUha Ydi efgL GdSda hUGdM GdNdas - (3jhSa Hf eMeO Hf eSYhO GdSQeOjs ((3eMeO Hf eMeO Hf GdNjVQi s)
(3ChdgG (B:s
(3bGd GdTjN LeGd GdOjf CHh GdeXaQ GdMeO ddg eLJHi ef CMH ef YHGOg bGd Gddg JYGdi (B( (3CdG Ef ChdjGA Gddg dGNha Ydjge hdG ge jMRfhf GdPjf BefhG hcGfhG jJbhf (B) s
(3BNQgG (B:s
(3GdGeGe VjGA GdOjf Hf GdfLjH YHO GdbGgQ Hf YHO Gddg GdSgQhQOi hgh djS ef Yeg hLjg GdOjf YeQ heG Jhajbi EdG HGddg Ydjg JhcdJ hEdjg eFGH hdG Mhd hdGbhI EdG HGddg GdYdi GdYXje hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG CQVg s
Keywords: (3GdJUha hGdBOGH GdTQYjIs